Deformation on Rainbow Massif, Mid‐Atlantic Ridge, Illuminated With Microearthquakes Detected by Machine Learning - Evan C. Anderson; Ross Parnell‐Turner; Robert A. Sohn; Wenyuan Fan (Geophysical Research Letters, 2025)
Abstract Oceanic detachment fault systems are characteristic of slow‐spreading mid‐ocean ridges, where reduced magma supply leads to increased extension by faulting and exhumation of oceanic core complexes (OCCs). OCCs have complicated structure reflecting the interplay between magmatic, hydrothermal, and tectonic processes. We use microearthquake data from a 9‐month ocean bottom seismometer deployment to image deformation structures in the Rainbow massif on the Mid‐Atlantic Ridge. Using a machine‐learning enabled workflow to obtain an earthquake catalog containing >68,000 events, we find seismicity occurred in distinct clusters that correlate with previously imaged velocity anomalies and dipping subsurface reflections. Our results are consistent with a dipping alteration front within the massif overlying late‐stage intrusions and suggest a transpressional fault accommodates a non‐transform offset north of the massif. Our results demonstrate OCCs continue to deform in a complex way after a detachment fault has been abandoned due to combined effects of tectonic stresses, magmatism, and alteration.